Respuesta :

Answer:

g(4) = [tex]\frac{5}{11}[/tex]

Step-by-step explanation:

Substitute x = 4 into g(x) , that is

g(4) = [tex]\frac{4^2-6}{3(4)+10}[/tex] = [tex]\frac{16-6}{12+10}[/tex] = [tex]\frac{10}{22}[/tex] = [tex]\frac{5}{11}[/tex]

>> Answer

_______

[tex] \: [/tex]

[tex] \sf{g(x) = \frac{ {x}^{2} - 6 }{3x + 10} }[/tex]

[tex] \sf{g(4) = \frac{ {4}^{2} - 6 }{3(4) + 10}} [/tex]

[tex] \sf{g(4) = \frac{16 - 6}{12 + 10}} [/tex]

[tex] \sf{g(4) = \frac{10}{22}} [/tex]

[tex] \sf{g(4) = \bold{\frac{5}{11}} }[/tex]